2020
DOI: 10.4236/ojbm.2020.82063
|View full text |Cite
|
Sign up to set email alerts
|

Consumer Behavior for Milk and Dairy Products as Daily Consumption Products in Every Household—The Case of Kosovo

Abstract: In our study, we used consumer behavior to study the buying and consuming patterns for milk and dairy products for households in Kosovo. The study uses data collected from consumers of milk and dairy products. Data obtained from the field were recorded and analyzed with the SPSS statistical program. The results of this study show that the date of production and the content of milk and dairy products are the most important factors that consumers consider when purchasing milk and dairy products. Moreover, superm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 10 publications
0
6
0
2
Order By: Relevance
“…Hence, most respondents consumed these products more than once a week and for breakfast and they considered important factor for decision-making process as price. According to Bytyqi et al (2020) observed that the date of production and the content of milk and dairy products were the most important factors that consumers considered when purchasing milk and dairy products. In addition, consumers were most likely to buy milk and dairy products twice a week.…”
Section: Review Of Literaturementioning
confidence: 99%
“…Hence, most respondents consumed these products more than once a week and for breakfast and they considered important factor for decision-making process as price. According to Bytyqi et al (2020) observed that the date of production and the content of milk and dairy products were the most important factors that consumers considered when purchasing milk and dairy products. In addition, consumers were most likely to buy milk and dairy products twice a week.…”
Section: Review Of Literaturementioning
confidence: 99%
“…La leche de cabra fluida y sus productos procesados son útiles como alimentos funcionales para el mantenimiento de la nutrición y salud de personas jóvenes y longevas, y especialmente para aquellas que padecen de alergia a la leche de vaca (Bytyqi et al, 2020;Sánchez et al, 2020). La Leche de cabra pude ser empleada para preparar una gran variedad de subproductos lácteos como lo son: quesos, yogurt, helados, leche condensada, mantequilla y leche en polvo.…”
Section: Introductionunclassified
“…Las rentabilidades obtenidas por los pequeños productores caprinos (denominados localmente como crianceros) a través de la producción de queso son bajas, dependiendo fuertemente de la climatología imperante (esto, considerando la situación de déficit hídrico permanente que afecta la región y el país) y realizada de manera informal, no implementándose en su inmensa mayoría sistemas de inocuidad alimentaria, trazabilidad ni formalización tributaria y/o sanitaria por parte de los productores. En cuanto al consumo de productos de leche de cabra, existen investigaciones sobre el comportamiento del consumidor en cuanto a la preferencia de la compra de productos lácteos y los factores que influyen en ese comportamiento y preferencia de los consumidores hacia la leche de cabra (Bytyqi et al, 2020;Shunekeyeva, 2020;Güney & Sangün, 2019;Šugrová, 2018).…”
Section: Introductionunclassified
“…Milk is a source of complete nutritions needed by human body (Bytyqi et al, 2020;Phan et al, 2020;Šugrová, 2018). However, the Pusat Data dan Sistem Informasi Pertanian (2019) states that the level of consumption of liquid milk in Indonesia is 11.09 liters/capita/year.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research on consumer preferences for dairy products (pure milk, processed cow milk, and processed goat milk) has been widely carried out. There are research on consumer behavior in buying dairy products (Bytyqi et al, 2020;Šugrová, 2018), the influencing factors on consumers' purchasing behaviors of milk products (Kaliji et al, 2019;Shunekeyeva, 2020), consumers' preference towards goat milk (Fanani & Thohari, 2018;Guney & Ocak, 2013;Solikah & Dewi, 2016), impacts of brands on consumers' decision (Kishokumar & Suganya, 2019;Velcovská & Larsen, 2021;Wijesinghe et al, 2020), and quality evaluation on production process of the powdered goat milk (Widodo et al, 2012).…”
Section: Introductionmentioning
confidence: 99%